2010
DOI: 10.1007/s12262-010-0166-5
|View full text |Cite
|
Sign up to set email alerts
|

Breast Tuberculosis- Clinical Spectrum and Management

Abstract: Objective of the study was to report the clinical spectrum, investigative profile and management of breast tuberculosis patients attending a tertiary care hospital. Breast tuberculosis is an uncommon form of tuberculosis. Knowledge of its varied clinical presentation and diagnostic modalities help in diagnosing this easily treatable disease. Retrospective data of 63 consecutive patients with breast tuberculosis was analyzed and information regarding demographic details, clinical presentation, cytology, histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
50
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 14 publications
3
50
0
2
Order By: Relevance
“…Direct extension from the chest wall (pleura or ribs) or and by inoculation of broken skin or duct openings can occur. Haematogenous spread is comparatively rare, Jah H et al [17] Studies reported axillary lymph node enlargement in 50%-70% cases of mammary tuberculosis which explained the retrograde lymphatic extension from axillary lymph nodes to breast [18].…”
Section: Discussionmentioning
confidence: 99%
“…Direct extension from the chest wall (pleura or ribs) or and by inoculation of broken skin or duct openings can occur. Haematogenous spread is comparatively rare, Jah H et al [17] Studies reported axillary lymph node enlargement in 50%-70% cases of mammary tuberculosis which explained the retrograde lymphatic extension from axillary lymph nodes to breast [18].…”
Section: Discussionmentioning
confidence: 99%
“…Se caracteriza por la ausencia de manifestaciones clínicas específicas; pero, la presentación más frecuente suele ser un nódulo unilateral de menos de un año de evolución (12)(13)(14)(15)(16)(17)(18). En 10-60 % de los casos se asocia dolor y puede confundirse con una lesión carcinomatosa ya que en su forma avanzada se acompaña de retracción de la piel o pezón (12)(13)(14)(15)(16)19).…”
Section: Discussionunclassified
“…In patients presenting with a mass accompanied by sinuses diagnosis becomes quite easy. Sinus tracks are pathognomonic of tuberculosis [7]. These are invariably associated with an underlying mass.…”
mentioning
confidence: 99%
“…This is a peculiar phenomenon typical of tuberculosis. Immunological tests in majority of cases are equivocal or inconclusive [7,8]. Hence they cannot be relied upon for diagnosis.…”
mentioning
confidence: 99%